Ritual and economy in a pre-Columbian chiefdom the El Cajón region of Honduras - Hirth, Kenneth 1949-; Hirth, Susan; Hasemann, George; Lara Pinto, Gloria 1952- (University Press of Colorado, 2023)
"An archaeological examination of the organization and ritual economy of a pre-Columbian chiefdom that developed in the El Cajón Region of central Honduras from 400 BC-AD 1000. Special attention is paid to jade and marble artifacts"
Keywords: Stammesgesellschaft; Archäologische Stätte; Kultur; Präkolumbische Zeit; Indigenes Volk; Ritual; Funde; Honduras; Chiefdoms / Honduras / Cajón Reservoir / Antiquities; Rites and ceremonies / Honduras / Cajón Reservoir / Antiquities; Excavations (Archaeology) / Honduras; Cajón Reservoir (Honduras) / Antiquities; Honduras / Antiquities; Honduras / Cajón Reservoir